Research integration using solar hybrid energy for small boat - Nguyen , Văn Tổng Em; Nguyen , Duy Anh; Le , Tất Hiển; Nguyen , Văn Trạng (Journal of Technical Education Science, 2021)
This paper presents research integration using solar hybrid energy for small inland boats. In this paper, survey data combined with expert evaluations are synthesized and analyzed to come up with a design of boat hull form and solar hybrid energy applications suitable to the characteristics of marine vehicles. The constraints of the draft, clearance, route, and width of canals all ensure the technical features according to the design recommendation. The design solution of a hybrid solar energy system including hardware and software for battery capacity, control system, and operation has also been compared and evaluated. The results show the feasibility of the study to integrate hybrid technology applying solar energy into small-sized vehicles operating in rivers and canals in Ho Chi Minh City and the Mekong Delta.